Role of the media in the inflation expectation formation process - Tetiana Yukhymenko (Graduate Institute of International and Development Studies, 2021)
This research highlights the role played by the media in the inflation expectations formation process of different types of respondents in Ukraine. Using a large news corpus and machine learning techniques I constructed news-based measures transforming text into quantitative indicators, which reflect news topics relevant to inflation expectations. As such, I found evidence that the different news topics have an impact on inflation expectations and can explain part of their variance. Thus, my results can help understand inflation expectations, especially as anchoring inflation expectations remains a key challenge for central banks.
Keywords: C55; C82; D84; E31; E58; 330; inflation expectations; natural language processing; textual data; machine learning